THU0327 ANTIBODIES AGAINST EXTRACTABLE NUCLEAR ANTIGENS (ENA) IN SCLERODERMA ARE NOT ONLY DIAGNOSTIC AND PROGNOSTIC TOOLS, BUT PATHOGENETIC REGULATORS INDUCING A PROFIBROTIC PHENOTYPE IN CULTURED SKIN FIBROBLASTS. (June 2019) - Corallo, Claudio; Cheleschi, Sara; Cutolo, Maurizio; Soldano, Stefano; Fioravanti, Antonella; Valenti, Roberto; Bellisai, Francesca; Nuti, Ranuccio; Giordano, Nicola
Abstract : Background: The importance of systemic sclerosis (SSc) autoantibodies for diagnosis has become increasingly recognized, as evidence by incorporation into the 2013 ACR/EULAR clinical classification criteria (1). Clear prognostic and phenotypic associations with cutaneous subtype and internal organ involvement have been extensively described (2). However, little is known about the potential of those autoantibodies to exert a direct pathogenetic role in the disease (3). Objectives: The aim of the study is to assess the potential pathogenetic role of anti-topo isomerase I (Topo-I) and anti-centromeric protein B (Cenp B) autoantibodies to induce pro-fibrotic markers in dermal fibroblasts. Methods: Dermal fibroblasts were isolated from unaffected and affected skin samples of (n=10) limited cutaneous SSc (LcSSc) patients, from affected skin samples of (n=10) diffuse cutaneous (DcSSc) patients and from (n=20) healthy subjects. Fibroblasts were stimulated with serum-isolated fractions of Topo-I, Cenp B and control IgGs in ratios 1:100 and 1:200 for 24 and 48 hours. Cells were also incubated with 10% SSc Topo-I +, Cenp B + whole serum and with 10% control serum for 24 and 48 hours. Viability was assessed by MTT test, while apoptosis was assessed by flow cytometry. Activation of pro-fibrotic genes ACTA2, COL1A1 and TAGLN was evaluated by quantitative-real-time-PCR (qPCR), while protein levels alpha-smooth-muscle actin (α-SMA), type-I-collagen (Col-I) and SM22 were assessed by immunocitochemistry (ICC). Results: MTT test showed that Cenp B (p<0.05) and with more extent Topo-I (p<0.01) IgGs reduced unaffected LcSSc and control fibroblast viability in a time- and dilution-dependent manner compared to control IgGs. Similar results were obtained with Cenp B + (p<0.05) and Topo-I + (p<0.01) sera compared to control sera. Flow cytometry analysis revealed that both Cenp B/Topo-I IgGs and Cenp B + /Topo-I + sera induce apoptosis in unaffected LcSSc and control fibroblasts only, while affected LcSSc/DcSSc fibroblasts showed apoptosis resistance. qPCR showed that basal levels of pro-fibrotic markers ACTA2, COL1A1 and TAGLN were upregulated in affected LcSSc/DcSSc fibroblasts compared to LcSSc unaffected and to control ones. Stimulation with Cenp B and Topo-I IgGs and with Cenp B + and Topo-I + sera statistically increased all the profibrotic markers compared to control IgGs (p<0.05) and to control sera (p<0.05). ICC proved that α-SMA, Col-1 and SM22 levels were upregulated in a time- and dilution-dependent manner in unaffected LcSSc and control fibroblasts upon stimulation with Cenp B and Topo-I IgGs and with Cenp B + and Topo-I + sera, while they remained stably high in affected LcSSc/DcSSc fibroblasts. Conclusion: This study demonstrates the pathogenetic role of antibodies targeting Topo-I and Cenp B to directly induce pro-fibrotic activation of fibroblasts. Therefore, besides the diagnostic and prognostic use of those autoantibodies in SSc, these data justify the importance of therapeutic use of immunosuppressive drugs in the early stages of the disease. References: [1] Denton CP. Advances in pathogenesis and treatment of systemic sclerosis. Clin Med (Lond) 2016;16:55-60. [2] Asano Y. Systemic Sclerosis. J Dermatol 2017; doi: 10.1111/1346-8138.14153. [3] Yayla ME, İlgen U, Düzgün N. An analysis of the relationship between autoantibodies and clinical findings in patients with systemic sclerosis. Turk J Med Sci 2018;48(1):10-15. Disclosure of Interests: None declared